LEGAL PROTECTION TO INDIVIDUAL RIGHTS IN LAND PROCUREMENT FOR PUBLIC INTEREST - Aartje Tehupeiory (Fakultas Hukum, Universitas Diponegoro, 2017)
In principle land procurement is done by a method that between the party requiring land and the right owner of land, whose land is required for public interest, under the principle applicable on land control and legal protection provided by the national law on land to the right to the land holders. In the legislation setting forth the land procurement for public interest a fair treatment is given to individual right so the legal protection and certainty for individuals in land procurement can be achieved. However, in the implementation the empirical cases get insufficient protection and fair treatment. There is no balance, equitability and harmony between the state’s right to control and protection to individual’s property right. On one side, the development for public interest is in an urgent need of sufficient lands, but on the other side individuals also need land for their life continuity. If by reason of development, the land is forcefully confiscated, it means ignoring the protection to individual right on land. Consequently, individuals and community get inadequate justice and protection, legal certainty. This writing is intended to analyze the role of legal protection to individual right in land procurement for public interest. By applying the statute approach method, the state’s role in providing legal protection to its citizens can be learnt. In conclusion there is lack of protection and respect to individual right and community provided on proportional basis because the delegation of state’s land control authority gives impression of extremely wide and great power.